Czy jest możliwa inna historia teorii (literatury)? - Ulicka, Danuta (Wydawnictwo Naukowe UAM, 2007)
This article binds several problems in which literature specialists are interested: in reference to the famous disputes about the theory of literature it indicates the need to redefine it, proposes is conceptualisation as a cultural opinion (utterance), justifies this need by the analysis of historical factual realisations of "theory" and conditions which reduced (monologised) them, and finally - it refers to the question of actuality of the "post-modern breakthrough" and the "turns" which announce it. The documentation of the proposed theses which revise the existing interpretations of history of the theory is being searched in the Central and East European literary studies of the beginning and the first decades of the 20th century, which has always been considered as the founding one for the discipline, however, sińce recently also as the source one for the analysis of the status of the utterances (opinions) expressed in it. The question asked in the title of this article about the possibility of another history of the theory resolves just in reference to the previous, nowadays mechanically enlivened projects of theory.
Is another history of the theory (of literature) possible?